Herbal Tea Fatty Acid Contents of Some Medicinal Plants Grown in Konya, Turkey - Tulukcu, Eray (Asian Journal of Chemistry, 2010)
In this study, 6 medicinal plants were generally used as herbal tea in Turkey. The medicinal plants are Hyssopus officinalis, Lavandula officinalis, Mentha piperita, Salvia sclareae L., Foeniculum vulgare Mill and Thymus vulgaris, respectively. The fatty acid compositions of medicinal plants were determined using gas chromatography (GC). 30 different fatty acids were determinated in the compositions of medicinal plants. At the end of experiment, the lowest total poly unsaturated fatty acid (PUFA) level was found in Hyssopus officinalis, the highest level was found in Lavandula officinalis. Oleic acid was identified as the major mono unsaturated fatty acid MUFA (4.8-35.61 % of total MUFAs). It was shown that the C 18:1 fatty acid played an important role on (MUFA) of Foeniculum vulgare Mill. Generally, linoleic acid and linolenic acid were the most abundant PUFA.